2018
DOI: 10.3390/ijms19071911
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning and Characterization of a meta/para-O-Methyltransferase from Lycoris aurea

Abstract: O-methyltransferases (OMTs) have been demonstrated to play key roles in the biosynthesis of plant secondary metabolites, such as alkaloids, isoprenoids, and phenolic compounds. Here, we isolated and characterized an OMT gene from Lycoris aurea (namely LaOMT1), based on our previous transcriptome sequencing data. Sequence alignment and phylogenetic analysis showed that LaOMT1 belongs to the class I OMT, and shares high identity to other known plant OMTs. Also, LaOMT1 is highly identical in its amino acid sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 79 publications
3
37
0
1
Order By: Relevance
“…Herb, is an ornamentally and medicinally important perennial herbaceous plant, belonging to the Amaryllidaceae family, from which there were a variety of Amaryllidaceae alkaloids found to exhibit medicinal values [22]. Previous studies of L. aurea have mainly focused on karyotype [23][24][25], physiological analysis [26,27], chemical composition [28][29][30], medicinal usage [31,32], and molecular aspects for gene cloning [33][34][35][36]. For example, several enzymes involved in Amaryllidaceae alkaloids biosynthesis, including cinnamate 4-hydroxylase [34], tyrosine decarboxylase [35] and norbelladine 4'-O-methyltransferase [36] have been identified.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Herb, is an ornamentally and medicinally important perennial herbaceous plant, belonging to the Amaryllidaceae family, from which there were a variety of Amaryllidaceae alkaloids found to exhibit medicinal values [22]. Previous studies of L. aurea have mainly focused on karyotype [23][24][25], physiological analysis [26,27], chemical composition [28][29][30], medicinal usage [31,32], and molecular aspects for gene cloning [33][34][35][36]. For example, several enzymes involved in Amaryllidaceae alkaloids biosynthesis, including cinnamate 4-hydroxylase [34], tyrosine decarboxylase [35] and norbelladine 4'-O-methyltransferase [36] have been identified.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies of L. aurea have mainly focused on karyotype [23][24][25], physiological analysis [26,27], chemical composition [28][29][30], medicinal usage [31,32], and molecular aspects for gene cloning [33][34][35][36]. For example, several enzymes involved in Amaryllidaceae alkaloids biosynthesis, including cinnamate 4-hydroxylase [34], tyrosine decarboxylase [35] and norbelladine 4'-O-methyltransferase [36] have been identified. Besides, although the induction effects of exogenous methyl jasmonate (MeJA) treatments on Amaryllidaceae alkaloids accumulation has been reported [37,38], little is known about the possible transcriptional or post-transcriptional regulation mechanism of this biological process in L. aurea.…”
Section: Introductionmentioning
confidence: 99%
“…pseudonarcissus TYDC, with an E-value of zero (Singh and Desgagne-Penix, 2017). Thus, we were able to find seven transcripts with E-values corresponding to genes encoding enzymes involved in Gal biosynthesis (Kilgore et al, 2014;Kilgore et al, 2016;Singh and Desgagne-Penix, 2017;Sun et al, 2018). In the central Gal biosynthetic pathway, sequence reads corresponding to OMT, C4H, and C3H were more abundant than those operating in precursor pathways including PAL, TYDC, and others ( Figure 5A).…”
Section: Gene Expression Analysis Of the Degs Involved In Gal Biosyntmentioning
confidence: 98%
“…NpN4OMT and LaOMT1 enzymes play key roles in the galanthamine biosynthesis pathway via the methylation of norbelladine to 4'-O-methylnorbelladine (Kilgore et al, 2014;Sun et al, 2018). Consequently, we also examined whether LlOMT exhibits catalytic activities.…”
Section: Llomt Enzyme Activity Assaysmentioning
confidence: 99%
“…The expression analyses showed that N4OMT is highly expressed in bulbs [ 59 , 65 , 70 , 72 ]. Interestingly, the O -methyltransferase found in Lycoris aurea (LauOMT1) was expressed at highest levels in flowers stalks and ovaries, and was demonstrated to have both para ’ and meta ’ O -methylation activities with a strong preference for the meta ’ position methylation [ 73 ].…”
Section: Biotechnological Production Of Amaryllidaceae Alkaloidsmentioning
confidence: 99%